Utilization of Mobille-Based Accounting Application and Google Business Profile of MSME - Wiralestari, Wiralestari; Arum, Enggar Diah Puspa; Wijaya, Rico; Friyani, Rita; Rosmeli, Rosmeli (PT FORMOSA CENDEKIA GLOBAL, 2024)
Micro, Small and Medium Enterprises (MSMEs) play an important role in supporting the Indonesian economy. However, many MSMEs still face challenges in effective financial management and digital marketing. This community service aims to improve the financial management and digital marketing capabilities of MSMEs through the use of mobile-based accounting applications and Google Business Profile. This activity involves hands-on training to MSME players to optimize the use of these two tools, which are expected to have a positive impact on improving the competitiveness and sustainability of their business. The results of this service show that MSMEs that apply this technology experience improvements in financial management and market access, thus making a significant contribution to local economic development.